The schooling response to a sustained increase in low-skill wages: Evidence from Spain 1989-2009 - Aitor Lacuesta; Sergio Puente; Ernesto Villanueva (SERIEs - Journal of the Spanish Economic Association, 2020)
The response of human capital accumulation to changes in the anticipated returns to schooling determines the type of skills supplied to the labor market, the productivity of future cohorts, and the evolution of inequality. Unlike the USA, the UK or Germany, Spain has experienced between 1995 and 2008 a drop in the returns to medium and tertiary education and, with a lag, a drop in schooling attainment of recent cohorts, providing the setup to estimate the response of different forms of human capital acquisition to relative increases in low-skill wages. We measure the expected returns to schooling using skill-specific wages bargained in collective agreements at the province-industry level. We argue that those wages are easily observable by youths and relatively insensitive to shifts in the supply of workers. Our preferred estimates suggest that a 10% increase in the ratio of wages of unskilled workers to the wages of mid-skill workers increases the fraction of males completing at most compulsory schooling by between 2 and 6.5 percentage points. The response is driven by males from less educated parents and comes at the expense of students from the academic high school track-rather than the vocational training track.
Keywords: J52; J24; 330; Collective contracts; Human capital; Investment in skills